The role of internet marketing in business development: a practical case of application of internet store technologies - Mshvidobadze, T. I (НТУ "ДП", 2024)
Results. Internet marketing and e-services are considered the latest areas of research that are of strategic importance to enterprises that have focused their efforts on the e-market. Research has shown that online consumer behavior is different from consumer behavior in a traditional market. This article presents a theoretical overview of the role of Internet marketing for business development and shows a practical example of creating an online store with a graphical user interface. The Internet offers the organization a wide range of opportunities for effective and practical business development, so the authors have considered the best ways to create Internet marketing for running a successful business. Результати. Інтернет-маркетинг та електронні послуги вважаються останніми напрямками досліджень, які мають стратегічне значення для підприємств, які спрямували свої зусилля на електронний ринок. Дослідження показали, що поведінка споживачів в Інтернеті відрізняється від поведінки споживачів на традиційному ринку. У цій статті представлено теоретичний огляд ролі Інтернет-маркетингу для розвитку бізнесу та показано практичний приклад створення інтернет-магазину з графічним інтерфейсом користувача. Інтернет пропонує організації широкі можливості для ефективного та практичного розвитку бізнесу, тому автори розглянули найкращі способи створення інтернет-маркетингу для ведення успішного бізнесу.
Роль інтернет-маркетингу в розвитку бізнесу: практичний кейс застосування технологій інтернет-магазину
Keywords: Internet marketing; information system; programming; information technologies; online store; Інтернет-маркетинг; інформаційна система; програмування; інформаційні технології; інтернет-магазин